2013
DOI: 10.1111/pace.12171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of an Implantable Cardioverter‐Defibrillator Lead with a Floating Atrial Sensing Dipole

Abstract: The studied ICD lead with a floating atrial sensing dipole met the predefined safety expectation and demonstrated appropriate atrial sensing performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
3
28
3
1
Order By: Relevance
“…Possible relationship between patients' height and AS amplitude was suggested [22]. In the present study, we did not find any connection between these variables.…”
Section: Discussioncontrasting
confidence: 34%
See 2 more Smart Citations
“…Possible relationship between patients' height and AS amplitude was suggested [22]. In the present study, we did not find any connection between these variables.…”
Section: Discussioncontrasting
confidence: 34%
“…Iori et al [21] showed stable AS during 200-day follow-up but the population of the study was limited to only 13 patients. In the largest, so far, multicenter study including 116 patients with ICD DX system, Safak et al [22] achieved appropriate AS in 93.8% of patients. In this study, mean preamplified P-wave amplitudes ranged from 5.0 mV to 6.1 mV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICDs. [23][24][25] One major limitation of the DX system is that it does not offer atrial pacing. However, data have shown that only 3% to 5% of patients implanted with a single-chamber ventricular ICD require an atrial lead upgrade for sinus node dysfunction during long term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] However, data on sensing during rapidly conducted AF are scarce, and the only comparative study reported more atrial sensing problems with this method than a conventional atrial electrode (36% versus 11%; P=0.002).…”
Section: Single-lead Atrial Sensing Icdmentioning
confidence: 99%